Role of computed tomography in evaluating asbestos related lung disease. Issue 11 (November 1989) - Lozewicz, S; Reznek, R H; Herdman, M; Dacie, J E; McLean, A; Davies, R J
Abstract : To find how computed tomography (CT) may be effectively used in individuals with suspected asbestos related lung disease 30 men with a history of exposure to asbestos were studied. All subjects underwent high kilovoltage posteroanterior and left lateral chest radiographs and chest CT. Eighteen were randomly selected asbestos workers referred for routine surveillance. The remaining 12 were patients who had been referred for investigation of respiratory symptoms or abnormal routine chest radiograph, or both, and found to have chest radiographic changes compatible with asbestos related lung disease. In the group referred for routine surveillance both pleural shadowing and pulmonary shadowing were shown on CT but not chest radiographs in only one case. Five were thought to have pleural shadowing on chest radiographs but this was confirmed on CT in only one case. All 12 patients referred for investigation showed pleural shadowing on chest radiographs; this was confirmed in all cases on CT which also showed unsuspected pulmonary shadowing in five cases. These findings suggest that it is not appropriate to use chest CT routinely in all asbestos workers referred for routine surveillance. When CT is used selectively in those with pleural shadowing on plain chest radiography, however, it is helpful in refuting or confirming the presence of pleural disease and may show unsuspected pulmonary shadowing.